Gender Relations on Quranic Interpretation in Indonesia (Interpretation Analysis on Turjuman Al-Mustafid's Tafsir, Al-Azhar's Tafsir, and Al-Misbah's Tafsir) - Dadan Rusmana; Nabilah Nuraini; Yayan Rahtikawati (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2023)
This paper attempts to picture the shift in discourse on gender relations in interpretive thinking in Indonesia by bringing together the interpretations of 'Abd al-Rauf Singkel, Hamka and M. Quraish Shihab. The selection of the three commentators was motivated by the difference in the period of writing the interpretations of the three. From this analysis, it is known that the interpretations of these three commentators on gender verses have points of similarities and differences. The interpretation of 'Abd al-Rauf Singkel in general follows the flow of traditional interpretations but his views are more moderate and tolerant, as seen in the issue of the origin of events and women's leadership. The shift in gender relations discourse is more visible in the interpretations of Hamka and M. Quraish Shihab. It seems to have its own interpretation, which does not fully follow the currents of traditional or contemporary commentators' views. This research is explored by comparative interpretation using critical discourse analysis method. From this research, it is found that modern and contemporary interpretations in Indonesia are more assertive in carrying out the discourse on Gender Equality Relations